Analisis Peramalan Anggaran Belanja Daerah Dengan Model Arima Dalam Upaya Pelaksanaan Green Economy Di Provinsi Jawa Barat - Firdayati Arifin, Nurul; Hutapea, Riauli Susilawaty (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Increasing issues related to environmental damage along with population growth each year encourage economic development that is more environmentally friendly (green economy). Until now, there is no precise regulation regarding the amount of environmental budget allocation, so the environmental expenditure budget is still minimal. This study aims to determine the best forecasting method to predict the regional budget for environmental functions in West Java province for 2022 – 2025. This research is a descriptive study with a quantitative and qualitative approach. The data used in this research is the realization of environmental spending in West Java Province from 1994 to 2021. Data analysis was performed using Eviews 9. The results of this study indicate that the ARIMA method is more appropriate than the exponential smoothing method in forecasting because it produces a much smaller error value with a MAPE value of 19.042%.